Operational Efficiency, The Risk of Finance and Liquidity Towards The Profitability of Syariah Banking - Handayani, Nisah; Atika,; Inayah, Nurul (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
The background of the research begins in 2020. In that year a large number of clients withdrew massive amount of their money out of the bank. The banks had not fulfilled their obligation to their clients which, in return, caused issues with their liquidity along with other problems pushing them towards the brink of the bankcruptcy. The research employs a quantitative approach. It uses secondary data obtained from annual report on the website issued by the Bank Umum Syariah (General Syariah Bank) as seen on the official site of OJK and the bank site within the period of 2018 and 2022. The applied data analysis of the research is quantitative analysis using eviews statistics -10. The result of the research shows that first, the operatioanl efficiency does not significantly affect the profitability of Syariah Banks. On the other hand finance risks pose a significant influence towards the profitability of Syariah Banks. It can be concluded that the liquidity risk is denied and that it has positive yet insignificant effects to the profitability of Syariah Banks